EVALUATION OF TEMPERAMENT CHARACTERISTICS IN A JUNIOR HANDBALL TEAM - C. ROMILĂ; S. TEODORESCU; Romanian-American University, Faculty of Physical Education, Sport and Kinetotherapy, Bucharest, Romania (Editura Universitatii Transilvania din Brasov, 2020)
Knowing a player's temperament can help the coach in the communication relationship between him and the player. First, the coach will know how to approach the subject to get a certain answer in practice or matches. Subjects were handball players born in 2005 or younger, at the category juniors III from Sporting Ghimbav Sports Club. The initial testing took place on 22nd December 2018 and 9th January 2019 and the final testing on 23rd November 2019. The method used is the application of psychological test, the Guide Belov for identifying the temperament, and interpretation of the results. The conclusions of the study have highlighted useful information on how to improve the training of the junior players.